Evaluation Of Investment In IoT Startup at PT TMI - Wiwit Hermawan; Kin Tjendrasa (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Garut, 2020)
Smartphone revolution, the rise of OTT (Over the Top) technology, and growth of mobile application drive explosion in data demand and erosion of legacy service, which voice and SMS (Short Messaging Service) revenue. It forces mobile telecommunication operators to explore new revenue sources through new business development by taking the opportunity across technology, media, and telecommunication (TMT). Telkomsel Mitra Inovasi (TMI), Telkomsel Corporate Venture Capital (CVC), conducts non-organic business development through investment in an early-stage startup from TMT sectors. January 2020, TMI followed in Series B1 funding of the Internet of Things (IoT) startup. The investment evaluation utilizes two factors which capital gain and incremental revenue to existing Telkomsel business. There is uncertainty in financial return on high-risk investments in a new startup company, and existing Telkomsel IoT provides smart connectivity services. However, connectivity will become increasingly commoditized, declining from 9% of total IoT revenue in 2018 to 5% in 2025. Consequently, Telkomsel IoT should expand its role to seize the incremental revenue opportunities. This research project uses discounted cash flow (DCF), secondary data to predict expected financial return after capturing possible risk investment for sound management decisions.